Human Fibrinogen Concentrate and Fresh Frozen Plasma in the Management of Severe Acquired Hypofibrinogenemia in Children With Acute Lymphoblastic Leukemia: Results of a Retrospective Survey. Issue 4 (May 2019) - Giordano, Paola; Grassi, Massimo; Saracco, Paola; Luciani, Matteo; Colombini, Antonella; Testi, Anna M.; Micalizzi, Concetta; Petruzziello, Fara; Putti, Maria C.; Casale, Fiorina; Consarino, Caterina; Mura, Rosa M.; et al.
Abstract : Objective of the Study: In this study we aimed to retrospectively evaluate how centers, belonging to the Associazione Italiana Ematologia e Oncologia Pediatrica (AIEOP), manage severe acquired hypofibrinogenemia in children with acute lymphoblastic leukemia, particularly evaluating the therapeutic role of human fibrinogen concentrate (HFC) and fresh frozen plasma (FFP). Methods: We conducted a survey among AIEOP centers; thereafter, we collected and analyzed data with regard to the treatment of episodes of severe acquired hypofibrinogenemia occurring during the induction and reinduction phases of the AIEOP-BFM ALL 2009 protocol. Results: In total, 15 of the 37 AIEOP centers invited to join the survey agreed to collect the data, with 10 and 5 centers declaring to react to severe acquired hypofibrinogenemia (<70 mg/dL) by administering HFC or FFP, respectively. Of the 150 episodes of severe hypofibrinogenemia occurring in 101 patients, 47.3% were treated with HFC and 52.7% with FFP, with a normalization of fibrinogen levels achieved in greater proportion and in a shorter amount of time in the HFC group as compared with the FFP group. None of the patients presented with bleeding or thrombosis during the observation period. Conclusions: Even with the limitations of the retrospective nature of this study, HFC seems to be a safe and effective alternative to FFP for replacement therapy in case of severe hypofibrinogenemia in children with acute lymphoblastic leukemia.